The association of protein intake (amount and type) with ovarian antral follicle counts among infertile women: results from the EARTH prospective study cohort. (10th April 2017) - Souter, I; Chiu, Y‐H; Batsis, M; Afeiche, MC; Williams, PL; Hauser, R; Chavarro, JE; ,
Abstract : Objective: To evaluate the association between protein intake (amount and type) and antral follicle count (AFC). Design: Prospective cohort. Setting: Academic fertility centre. Population: Two hundred and sixty‐five women undergoing fertility treatments at an academic fertility centre and participating in an ongoing study on environment and reproductive health. Methods: We measured AFC in ultrasonographic evaluation among women undergoing infertility treatments. Women completed a previously validated semi‐quantitative food frequency questionnaire. We used Poisson regression to evaluate the relation between protein intake and AFC while adjusting for age, body mass index, race, smoking status, and total energy intake. Main outcome measures: Antral follicle count. Results: Among 265 women (mean age: 35.0 ± 3.9 years, 85% Caucasian), total protein intake (% energy) was unrelated to AFC. When protein from different food sources was considered separately, we found a negative association between dairy protein intake and AFC. The mean AFC was 14.4% (3.9–23.7%) lower for women in the highest quintile of dairy protein intake than for women in the bottom quintile after adjusting for potential confounders ( P ‐trend = 0.04). This association was stronger among women who had never smoked ( P ‐trend = 0.002) but was not observed among previous smokers ( P ‐trend = 0.36). There were no associations between protein intake from either non‐dairy animal or vegetable sources and AFC. Conclusion: Higher dairy protein intake (≥5.24% of energy) was associated with lower antral follicle counts among women presenting for infertility treatment. These findings should be further investigated in prospective studies also designed to clarify the biology underlying the observed associations. Tweetable abstract: Higher dairy protein intake was associated with lower antral follicle counts in an infertile population. Tweetable abstract: Higher dairy protein intake was associated with lower antral follicle counts in an infertile population.